Flavonoids of Polygonum hydropiper L. attenuates lipopolysaccharide-induced inflammatory injury via suppressing phosphorylation in MAPKs pathways. Issue 1 (December 2015) - Tao, Junyu; Wei, Yingyi; Hu, Tingjun
Abstract Background Polygonum hydropiper L. is widely used as a traditional remedy for the treatment of dysentery, gastroenteritis. It has been used to relieve swelling and pain, dispel wind and remove dampness, eliminate abundant phlegm and inflammatory for a long time. Previous study showed that antioxidants especially flavonoids pretreatment alleviated sepsis-induced injury in vitro and in vivo. In the present study, the possible anti-inflammatory effect of flavonoids from normal butanol fraction ofPolygonum hydropiper L. extract (FNP) against inflammation induced by lipopolysaccharide (LPS) was evaluated in vivo and in vitro. Methods The content of total flavonoid of FNP was determined by the aluminum colorimetric method. The content of rutin, quercetin and quercitrin was determined by HPLC method. Mice received FNP orally 3 days before an intra-peritoneal (i.p.) injection of lipopolysaccharide (LPS). Total superoxidase dismutase (T-SOD), total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-PX), glutathione (GSH), myeloperoxidase (MPO) and malondialdehyde (MDA) levels were measured. Tumor necrosis factor-α levels in serum and tissue was measured. mRNA expressions of pro-inflammatory cytokines in lung were assessed by Real-Time PCR. Histopathological changes were evaluated in lung, ileum and colon. We also investigated FNP on reactive oxygen species (ROS), nitric oxide (NO) and pro-inflammatory cytokines (TNF-α, IL-1β, IL-6 and IL-8) production, inducible nitric oxide synthase (iNOS), Cyclooxygenase-2 (COX-2) protein expression, phosphorylation of MAPKs and AMPK in LPS-stimulated RAW264.7 cells. Results FNP increased the levels of T-SOD, T-AOC, GSH-PX and GSH, decreased the levels of TNF-α, MPO and MDA, attenuate the histopathological lesion in LPS-stimulated mice. FNP inhibited production of inflammatory cytokines, ROS and NO, protein expressions of iNOS and COX-2, phosphorylation of ERK, JNK and c-JUN in MAPKs, promoted phosphorylation of AMPKα suppressed by LPS. Conclusion These results suggested in vivo anti-inflammatory activities of FNP might contributed to its enhancement in antioxidant capacity, its inhibitory effects may be mediated by inhibiting the phosphorylation of JNK, ERK and c-JUN in MAPKs signaling pathways.